Symposium 5: Teachers' Views on Assessment in Higher Education - Oberg, Hans; Zenios, Maria; Parhoma, Gale (Proceedings of the International Conference on Networked Learning, 2010)
From a social constructivist viewpoint, learning is a constructive act of the learner. Several different assessment methods are used in assessing students, which have implications when discussing knowledge construction in higher education. Teachers’ views about different formats and methods of assessment were examined by interviewing teachers in higher education. This work-in-progress suggests that students' perceptions about assessment have considerable influence on their approaches to learning, but that organizational and teachers’ perceptions of institutional objectives are significant factors in choosing assessment methods. Although the teachers interviewed agree in the constructive act of the learner, the assessment is still more of a teacher-centred process for teachers with little experience of networked learning environments. This is also partly because of the restraints of university examination rules, as well as universities adaptation to the Bologna Declaration (1999). Being gradually acculturated and assimilated into the networked learning community in the form of an apprenticeship should help in making teachers more inclined towards a student-centred approach and to using peer assessment.